Duelo por separación amorosa como detonante de condiciones psicosomáticas (2024)
The purpose of this research work is to raise awareness about the impact of emotional breakups, using tools to identify the trigger and thus mitigate the trigger of psychosomatic conditions due to the absence of love. Throughout the academic process, the emotional instability of young people can be evident, and they are linked to a problem to which the required importance is not given, given that in recent years suffering from a love breakup has become normalized, and If there are no adequate tools, it is necessary to identify the main factor of the somatic symptoms that this rupture generates by not being coped with in the correct way. The semi-structured interview (Scheele & Groeben, 1988), Likert (Likert, 1932) scale and direct observation are the instruments that were carried out for the qualitative research. Which responded to the stated objectives. The interview was conducted with 3 people who experienced grief due to romantic separation. It was possible to verify how grief in emotional breakups is a psychosomatic trigger in human beings, triggering general anxiety, physical and emotional damage, isolating people, thus affecting their interpersonal relationships.